Efektivitas Pemanfaatan QGIS Dalam Pembuatan Peta Inventarisasi Perlengkapan Jalan - Wijayanthi, Kanthi; Basuki, Ahmad; Tohom, Frans (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2021)
In the field of road traffic and transportation, road inventory activities are needed to monitor or monitor the condition of road equipment. The proper data collection will facilitate evaluation and supervision by managers or supervisors of traffic and road transportation. The data collection of road equipment inventory data can be compiled manually or electronically, which is integrated with the road equipment information system. One of the electronic data collections is by utilizing QGIS, which is one part of the Geographic Information System (GIS). This study aims to measure the effectiveness of using QGIS in making road equipment inventory maps using survey data and questionnaires to determine the difference between manual inventory data collection and WebGIS-based inventory data collection. Data analysis used SPSS calculation to test data validity, reliability, normality, Wilcoxon test and N-Gain Score test. From this data, it is found that the use of QGIS in road equipment inventory mapping has an average effectiveness of 60.26%, with the interpretation criteria being quite effective.